Thermal and Catalytic Pyrolysis of Plastic Waste: Catalysts Characterization and Properties of the Liquid Products - Zahraa Hussein; Zaidoon Shakor; Mohammed Alzuhairi (Journal of Applied Sciences and Nanotechnology, 2022)
Nowadays, sustainable energies can be found by thermal and catalytic pyrolysis of plastic waste. This study uses high-density polyethylene (HDPE), low-density polyethylene (LDPE), polypropylene (PP), polystyrene (PS), and polyethylene terephthalate (PET) to investigate thermal and catalytic pyrolysis using a stainless-steel semi-batch reactor at different conditions: Temperatures (350 - 500°C) and residence times (60, 90, and 120 min). The catalysts were undergone to different characterization techniques such as EDX, SEM, and BET that revealed the PR.9 catalyst consists of Cobalt, Molybdenum, and Platinum loaded on Al2O3. Whereas, the chemical compositions of Platinum RG-412 catalyst contain Chlorine and Platinum. The SEM analysis showed that the PR.9 catalyst is more active than RG-412 for the degradation of plastics. In addition, the properties of the liquid products like density, API, and viscosity were studied. As a result, the properties of the liquid produced by the plastic pyrolysis were similar that those produced from the petroleum refineries. The API findings declared that almost all of the liquids produced were light products, which contain mainly diesel oil, gas oil, kerosene, and gasoline.